Modifying capture techniques for wild Laysan Teal Anas laysanensis - Breeden, Jr., James H.; Goodale, Kelly L. (Wildfowl, 2021)
The Laysan Teal Anas laysanensis is endemic to the Hawaiian archipelago with wild populations currently occurring on Laysan Island, Midway Atoll and Kure Atoll. Previous Laysan Teal translocations expanded their range by establishing new populations to reduce extinction risk. In 2015 the House Mouse Mus musculus was documented feeding on live Laysan Albatross Phoebastria immutabilis and a plan was developed to eradicate mice from the atoll. To protect Laysan Teal from non-target mortality during a mouse eradication, new capture techniques were developed to move and isolate Laysan Teal temporarily on a mouse-free island within Midway Atoll until the ducks were no longer at risk of secondary and primary poisoning. Here we describe modifications to techniques previously used for the capture of Laysan Teal. These techniques can be applied to the other waterfowl and adapted for other species.